Calculation of the Tunneling Current for Atom-sized Quantum Dot with Scanning Tunneling Microscope - Ajeel, Fouad Nimr (University of Thi-Qar Journal of Science, 2014)
In this work, the tunneling current of adsorbed atom-sized quantum dot on metal surface with scanning tunneling microscope (STM) is calculated using nonequilibrium Green’s function method of Keldysh. It is found that the correction to the tunneling current is expressed in terms of the transmission probability, where the correction is negative for the elastic part of the current and positive for the inelastic one. Depending on our calculations, we conclude that the position of electronic state of quantum dot, the vibrational mode energy, the strength of electron-vibration coupling and temperature, which important parameters to determine the physical features responsible for the processes concerned the nanostructure that are performed on the solid surface